2003
DOI: 10.3349/ymj.2003.44.2.215
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Frontal Sinus in Turkish Individuals

Abstract: The frontal sinus has been used for personal identification since the early part of the 20th century as a result of its tremendous interindividual variation. The frontal sinus is present in approximately 90% of adults. However, some populations have a higher proportion of people without a frontal sinus. This study investigated the frequency of the absence of frontal sinuses in Turkish individuals. The present study was performed retrospectively on the CT scans of the paranasal sinuses in the axial and coronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
74
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 0 publications
9
74
0
Order By: Relevance
“…The frontal sinuses are located in the frontal bone, and similarly to the majority of cranial hollow cavities (sphenoidal sinus, frontal sinus, ethmoid cells and maxillary sinus) are pneumatics cavities covered by a mucous membrane with direct or indirect communication with the respiratory system (Quatrehomme et al, 1996;Aydinlioglu et al, 2003;Silva et al).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The frontal sinuses are located in the frontal bone, and similarly to the majority of cranial hollow cavities (sphenoidal sinus, frontal sinus, ethmoid cells and maxillary sinus) are pneumatics cavities covered by a mucous membrane with direct or indirect communication with the respiratory system (Quatrehomme et al, 1996;Aydinlioglu et al, 2003;Silva et al).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is the last one to develop among the paranasal sinuses. It has been reported that frontal sinus is absent bilaterally in 3-4 to 10 % of population [1] and the frequency is found to be quite high in Alaskan Eskimos(25 % males, 36 % females) and in Canadian Eskimos(43 % males, 40 % females) [3,4]. In addition to it, the configuration and development of frontal sinus within each population also depends upon the constitutional (age, gender, hormones and craniofacial configuration) and the environmental factors (climatic conditions and local inflammation) [1,5,6].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that frontal sinus is absent bilaterally in 3-4 to 10 % of population [1] and the frequency is found to be quite high in Alaskan Eskimos(25 % males, 36 % females) and in Canadian Eskimos(43 % males, 40 % females) [3,4]. In addition to it, the configuration and development of frontal sinus within each population also depends upon the constitutional (age, gender, hormones and craniofacial configuration) and the environmental factors (climatic conditions and local inflammation) [1,5,6]. As per the literature and previous researchers, it has been reported that the frequency of bilateral frontal sinus aplasia is extremely rare and occurs more in young females as compared to males [1,3,5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations